Reshaping procedures for the surgical management of corneal ectasia. Issue 4 (April 2015) - Ziaei, Mohammed; Barsam, Allon; Shamie, Neda; Vroman, David; Kim, Terry; Donnenfeld, Eric D.; Holland, Edward J.; Kanellopoulos, John; Mah, Francis S.; Randleman, Bradley J.; Daya, Sheraz; Güell, Jose
Abstract : N/A: Corneal ectasia is a progressive, degenerative, and noninflammatory thinning disorder of the cornea. Recently developed corneal reshaping techniques have expanded the treatment armamentarium available to the corneal specialist by offering effective nontransplant options. This review summarizes the current evidence base for corneal collagen crosslinking, topography‐guided photorefractive keratectomy, and intrastromal corneal ring segment implantation for the treatment of corneal ectasia by analyzing the data published between the years 2000 and 2014. Financial Disclosure : No author has a financial or proprietary interest in any material or method mentioned.